Formulasi Pengaturan Tahapan Pra Kontrak dalam Proses Pembentukan Kontrak di Indonesia - Ardyo, Bebeto (JURNAL YUSTIKA: MEDIA HUKUM DAN KEADILAN, 2019)
The increasement of human needs in society goes hand in hand with the development of technology. To meet these needs, there must be interaction between people which sometimes has the potential to cause disputes. That’s why a contract is needed. The existence of a contract guarantees legal certainty regarding protection of the rights of the parties and also the obligations that they must fulfill. There are several stages of contract formation which consist of pre-contract and agreement between the parties. According to the system in the Book III of Indonesia’s Code of Civil Law, consensus is the base for the formation of contract that means once the agreement has reached between the parties then a contract is formed. Indonesia’s Code of Civil Law doesn’t yet regulate pre-contract stages of contract formation, even though these stages are equally important. The regulation of pre-contract stages are usually set in the common law system, but along with the times, the regulation of pre-contract stages should also be regulated in the civil law system. As a comparison, Het Nieuw Burgerlijke Wetboek (New Civil Code of Netherlands) has already regulated that pre-contract stages, although the Netherlands is a country that implements civil law system. The pre-contract stages are very important to be regulated in Indonesia because there are many potential pre-contractual issues. This paper aims to formulate the outline of what needs to be regulated in the pre-contract regulations. Keywords : Interaction, Contract, Formation, Civil Code